Interaction of Satisfaction level, work Life Balance and Work Environment by motivation in Higher Education professionals, in National Capital Region of Delhi - Ashu Singh, Sweta Singh, (International Journal of Scientific Research and Management (IJSRM), 2017)
Higher education to service quality education institutes by professionals in Delhi & NCR Region, The data were collected in two phases and are based on the 285 samples collected from selected professors considered simultaneously. The Gap analysis shows that self-assessment with efforts were 2: 3.34 similar to motivation and job security 2:3.1and larger satisfaction level for work life. The relation of gap score is proportional to Work Life Balance, Motivation and Job Security. Interestingly the neutrality was higher by motivation. Dis-satisfaction level was higher in experience range of 60-96 months. Log values will also help for improvement to researchers. This data insight institutes to make their policies